Stem Cells in Amyotrophic Lateral Sclerosis: Motor Neuron Protection or Replacement? - Silani, V.; Calzarossa, C.; Cova, L.; Ticozzi, N. (CNS & Neurological Disorders - Drug Targets, 2010)
Given the lack of effective drug treatments for amyotrophic lateral sclerosis (ALS), compelling preclinical data on stem cell research has targeted this disease as a candidate for stem cell treatment. Stem cell transplantation has been effective in several animal models, but the underlying biological pathways of restorative processes are still unresolved. Several mechanisms such as cell fusion, neurotrophic factor release, endogenous stem cell proliferation, and transdifferentiation may explain positive therapeutic results in preclinical animal models, in addition to replacement of lost motor neurons. The clinical target in ALS has shifted from being neuroncentered to focus on the interaction between motor neurons and non-neuronal cells (mainly astroglial or microglial). In fact, one of the fundamental unanswered questions in ALS is whether and how much motor neuron death depends on neighboring cells, and how wildtype non-neuronal cells may protect motor neurons expressing an ALS-causing mutation. Lately, motor neuron replacement has been successfully achieved in animal models with reinnervation of the muscle target. Even if many biological issues need to be solved in preclinical models, preliminary stem cell transplantation trials have been performed in ALS patients with conflicting results. The review discusses relevant topics regarding the application of stem cell research to ALS focusing on their therapeutic relevance and mechanisms of action.
Keywords: protection